2016
DOI: 10.1007/s00432-016-2250-0
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein-2 is overexpressed in non-small cell lung cancer tissues and its knockdown suppresses NSCLC growth by regulation of p27 and CDK2

Abstract: This study revealed the importance of Dsg2 in suppression of NSCLC development and progression. Further studies will explore whether restoration of Dsg2 expression is a novel strategy in control of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 38 publications
4
52
0
2
Order By: Relevance
“…32 A study showed that downregulation of DSG2 expression in colonic adenocarcinoma cell lines led to growth inhibition both in vitro and in vivo, which highlighted the essential role of the cell adhesion protein in controlling the growth of cancer cell. Consistent with these findings that DSG2 was found to be overexpressed in skin cancer, 33 lung cancer, 34 and head and neck cancer. 35 The possible mechanism is downregulated DSG2 inhibited epidermal growth factor receptor (EGFR) signaling and cell proliferation through altered phosphorylation of EGFR and downstream extracellular signalregulated kinase activation in parallel with inhibited EGFR receptor internalization.…”
Section: Discussionsupporting
confidence: 83%
“…32 A study showed that downregulation of DSG2 expression in colonic adenocarcinoma cell lines led to growth inhibition both in vitro and in vivo, which highlighted the essential role of the cell adhesion protein in controlling the growth of cancer cell. Consistent with these findings that DSG2 was found to be overexpressed in skin cancer, 33 lung cancer, 34 and head and neck cancer. 35 The possible mechanism is downregulated DSG2 inhibited epidermal growth factor receptor (EGFR) signaling and cell proliferation through altered phosphorylation of EGFR and downstream extracellular signalregulated kinase activation in parallel with inhibited EGFR receptor internalization.…”
Section: Discussionsupporting
confidence: 83%
“…In particular, desmosomal cadherin is known to promote cell growth, migration, and invasion through regulation of the signaling of cyclin-dependent kinase 2 (CDK-2), activator protein 1 (AP-1), and protein kinase C (PKC). 19,20 The expression of E-cadherin is limited to the epithelial cells of pterygium head and not detected in the normal cornea and conjunctiva. 21 Thus, our findings indicate that desmosomes between PECs not only provide hyperadhesive intercellular junctions, but may also facilitate the signal transduction mediating aggregation-dependent cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant protein is desmoglein-2. It has been reported that desmoglein-2 is overexpressed in NSCLC tissues and induce NSCLC growth by regulating p27 and CDK2 [105]. The next most enriched protein is EGFR.…”
Section: Lung Cancermentioning
confidence: 99%
“…Drug and chemotherapy resistance [97] TGF-β1 Drug resistance [98] TPRC5 Chemotherapy resistance [99] UCH-L1 Chemotherapy resistance [100] Nephronectin Induce tumor mestasis [101] Caveolin-1 Enriched in metastasized cancer cell [36] Periostin Enriched in metastasized cancer cell [102] Myoferlin Enriched in metastasized cancer cell [31] Lung Cancer Mucin 5AC, B Lung cancer relapse and metastasis [103,104] Desmoglein-2 overspressed in non small cell lung cancer and induce cell growth [105] EGFR Oncogene in lung cancer [106,111,113,114] LRG1 Induce angiogenesis [108] Tim-3 Induce anti-tumor immune response [110] NY-SEO-1 Overexpressed in lung cancer [111] [111] EpCam Overexpressed in lung cancer [111] SGRN Overexpressed in lung cancer [112] TPM3 Overexpressed in lung cancer [112] THBS1 Overexpressed in lung cancer [112] HUWE1 Overexpressed in lung cancer [112] MUC 1 Overexpressed in lung cancer [112] Colon Cancer…”
Section: Gstp1mentioning
confidence: 99%